7r+2=5(r-4)whatisx

Simple and best practice solution for 7r+2=5(r-4)whatisx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7r+2=5(r-4)whatisx equation:


Simplifying
7r + 2 = 5(r + -4) * whatisx

Reorder the terms:
2 + 7r = 5(r + -4) * whatisx

Reorder the terms:
2 + 7r = 5(-4 + r) * whatisx

Reorder the terms for easier multiplication:
2 + 7r = 5ahistwx(-4 + r)
2 + 7r = (-4 * 5ahistwx + r * 5ahistwx)

Reorder the terms:
2 + 7r = (5ahirstwx + -20ahistwx)
2 + 7r = (5ahirstwx + -20ahistwx)

Solving
2 + 7r = 5ahirstwx + -20ahistwx

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-5ahirstwx' to each side of the equation.
2 + -5ahirstwx + 7r = 5ahirstwx + -5ahirstwx + -20ahistwx

Combine like terms: 5ahirstwx + -5ahirstwx = 0
2 + -5ahirstwx + 7r = 0 + -20ahistwx
2 + -5ahirstwx + 7r = -20ahistwx

Add '-2' to each side of the equation.
2 + -5ahirstwx + -2 + 7r = -2 + -20ahistwx

Reorder the terms:
2 + -2 + -5ahirstwx + 7r = -2 + -20ahistwx

Combine like terms: 2 + -2 = 0
0 + -5ahirstwx + 7r = -2 + -20ahistwx
-5ahirstwx + 7r = -2 + -20ahistwx

Reorder the terms:
2 + -5ahirstwx + 20ahistwx + 7r = -2 + -20ahistwx + 2 + 20ahistwx

Reorder the terms:
2 + -5ahirstwx + 20ahistwx + 7r = -2 + 2 + -20ahistwx + 20ahistwx

Combine like terms: -2 + 2 = 0
2 + -5ahirstwx + 20ahistwx + 7r = 0 + -20ahistwx + 20ahistwx
2 + -5ahirstwx + 20ahistwx + 7r = -20ahistwx + 20ahistwx

Combine like terms: -20ahistwx + 20ahistwx = 0
2 + -5ahirstwx + 20ahistwx + 7r = 0

The solution to this equation could not be determined.

See similar equations:

| 5x(3x+5)=10 | | w=21+2p | | 3.2x+14=-4 | | 163.2+23.84x-16x^2=4 | | 5x(3x+5)=5 | | 5=5a | | 12rs+5r-6s= | | x^2-490x+5000=0 | | 5+4b=20 | | 9-6x=26 | | 3y-2=5y+6 | | -3(4+6n)-7=8n-7-14 | | -5n-6+4n=-14 | | -6(y-2)=2y-24 | | -6(7-2)=2y-24 | | 6=2+d | | -5u-46=-8(u+8) | | Y-2=2.6(x-0) | | 45-(4-2y-4(y+7))=-4(1+3y)-(4-3(y+2)-2(2y-5)) | | -11+x=-7x-8(x+1) | | -37+7=-9y+49 | | -37+7=-97+49 | | 10x-30+7x=13x | | 13-3v=8v+2 | | -5v+8(v+3)=39 | | 7x^2+16x=192 | | 3(w-8)+3w=-18 | | 18n-24t= | | 7=3y+y-8 | | 6(y+3)+2y=-38 | | X-2+x-3=123 | | 6x-9x+9=x-7+16 |

Equations solver categories